Characterisation of Precipitates in a Mg-6Gd-1Zn-0,6Zr (Wt%) Casting Alloy - J. F. Nie (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Mechanical properties of precipitation hardenable magnesium alloys depend critically on the chemistry, structure, morphology, orientation and distribution of strengthening precipitates. It is therefore important to gain an improved understanding of these information and their correlations with mechanical properties. Our recent studies indicate that additions of 1-2 wt% of Zn to a Mg-6wt%Gd alloy result in a substantial enhancement in precipitation hardening and in creep resistance. If the strength and creep resistance of the resulting ternary alloy are to be further enhanced for commercial applications, then a detailed characterisation of the strengthening precipitates in these alloys is required. In the present study, the precipitates formed in a Mg-6Gd-1Zn-0.6Zr (wt%) alloy, peaked aged at 250°C, have been characterised in detail using transmission electron microscopy and 3-dimensional atom probe field-ion microscopy. It is found the peak-aged microstructure contains a dense and uniform distribution of precipitate plates that form on the basal plane of the matrix phase and are typically less than 1 nm in thickness. Detailed analyses of the structure and composition of these basal precipitate plates will be presented and discussed in the context of previous work on other Mg-RE¬Zn alloys of similar compositions.